Effect of Copper Addition on Mechanical Properties and Electrical Conductivity of PP/C-Cu Bipolar Plate Composites - Zulfia, Anne; Abimanyu, Taufik; Dalam, Verina Warga (UI Scholars Hub, 2011)
Effect of Copper Addition on Mechanical Properties and Electrical Conductivity of PP/C-Cu Bipolar Plate Composites. Bipolar plate is a major component in PEM fuel cell which possess main function of collecting and removing electrons from anode to cathode. Therefore, materials for bipolar plates produced must have high electrical conductivity. To obtain bipolar plate materials which is cheap, lightweight and high conductivity, so it is developed bipolar plates material based on PP/C-Cu composite. PP/C-Cu composites has been made by mixing all materials then compounding, rheomix, hot blending and hot press. Cu (Copper) has been used various from 0.1 wt%, 1 wt% to 2 wt% to increase electrical conductivity of PP/C-Cu composite. It is found that the effect of Cu addition in PP/C-Cu composite has increased tensile strength, flexural strength, flexural modulus, tensile modulus, elongation, electrical conductivity and decreasde porosity, unfortunately the value of electrical conductivity was still lower than standard requirement for bipolar plate fuel cell.